2014
DOI: 10.1556/jfc-d-13-00016
|View full text |Cite
|
Sign up to set email alerts
|

Control of Hazardous Processes in Flow: Synthesis of 2-Nitroethanol

Abstract: After a short section of safety aspects related to 2-nitroethanol, the paper describes a powerful methodology for developing flow processes based on a proof of concept (1), an optimization and modeling analysis (2), and a long run study in a mini-plant (3). The proof of concept is the initial stage where the solubilities and concentrations are fixed, taking into account the rough kinetics with a mass transfer understanding. It is followed by a complete kinetic analysis including activation energy to model the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Similar concepts were applied by the same authors to a full platform of organic reactions carried out under cryogenic conditions [148]. Finally, an example of Grignard reaction in microreactors confirm that it is possible to effectively control the hot spot [149].…”
Section: Safety Issuesmentioning
confidence: 64%
“…Similar concepts were applied by the same authors to a full platform of organic reactions carried out under cryogenic conditions [148]. Finally, an example of Grignard reaction in microreactors confirm that it is possible to effectively control the hot spot [149].…”
Section: Safety Issuesmentioning
confidence: 64%
“…The CSTR flow pattern is quite useful when the reaction is very fast and the selectivity is not negatively influenced by the mixed flow regime, such as for acid-base precipitations [46]. A CSTR is a pragmatic approach to overcome the problem associated with solids handling, but its mixed flow pattern has inherent disadvantages relative to the near plug flow pattern that can be achieved in the Coil and Plate reactors.…”
Section: Liquid-solid Systemsmentioning
confidence: 99%
“…Moreover, process safety can be inherently increased when handling small amounts of hazardous chemicals at one point of time in a continuous-mode production campaign, compared with a batch production campaign of equal capacity [7,8]. Various research groups from both industry and academia recently demonstrated the applicability of continuous production concepts for fine chemicals and pharmaceuticals in dedicated examples [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%